Future Directions - Soares, António S.; Chand, Manish (Clinics in Colon and Rectal Surgery, 2020)
Transanal total mesorectal excision (taTME) is a novel technique that has evolved over the years to address the challenges of low rectal cancer surgery by applying the principles and benefits of laparoscopic surgery to more historic transanal techniques. It has been popularized through its use in rectal cancer, but the transanal approach is slowly being expanded to tackle different clinical scenarios including benign conditions such as inflammatory bowel disease and endometriosis. For all of these new indications, it is the desire to access and begin the dissection in native tissue beyond the pathology which makes this approach applicable to other diseases where anatomy can be challenging. Training pathways to safely introduce taTME in a standardized manner are being developed and implemented in a bid to ensure adequate training to all the surgeons using this technique and thus minimize complications and patient morbidity. The future directions of this promising technique include the use of image and optical technological enhancement to aid navigation, the use of pneumorectum stabilization, and perhaps the use of fluorescence as a safety improvement. Developments have come also from the field of robotics. After a demonstration of feasibility in cadaver models, a growing experience has been gathered in the robotic approach to taTME, covered in the last part of this chapter.
Keywords: taTME; safety; navigation; fluorescence